PENGEMBANGAN VIDEO ANIMASI BERBASIS POWTOON UNTUK MODEL PEMBELAJARAN FLIPPED CLASSROOM PADA MATERI TERMODINAMIKA - Khusnul Basriyah; Dwi Sulisworo (Universitas Muhammadiyah Semarang, 2018)
This study aims to develop a Powtoon-based animated video for Flippedclassroom learning models on thermodynamic materials. his type of research is ADDIE, which aims to produce a product with product validation from material experts, media experts, and Physical Science Teachers. assessment from material experts with a feasibility level of 85.93%, from media experts 81.33%, while from science physics teachers 81.6%. The results of the assessment of 30 students as a trial of the feasibility of powtoon video obtained results from the concept of video 81.62%, video as a reference material 86.27%, motivating students to study harder 82.35%, and video design 91.18%, from the feasibility results concluded that this media was categorized as feasible as a learning medium. Keywords: Powtoon, Flipped classroom,Termodinamika, Video Animasi